Estrogen-induced chromatin looping changes identify a subset of functional regulatory elements - Abewe, Hosiana; Richey, Alexandra; Vahrenkamp, Jeffery M.; Ginley-Hidinger, Matthew; Rush, Craig M.; Kitchen, Noel; Zhang, Xiaoyang; Gertz, Jason (Genome Research, 2025)
Transcriptional enhancers can regulate individual or multiple genes through long-range three-dimensional (3D) genome interactions, and these interactions are commonly altered in cancer. Yet, the functional relationship between changes in 3D genome interactions associated with regulatory regions and differential gene expression appears context-dependent. In this study, we used HiChIP to capture changes in 3D genome interactions between active regulatory regions of endometrial cancer cells in response to estrogen treatment and uncovered significant differential long-range interactions strongly enriched for estrogen receptor alpha (ER, also known as ESR1)–bound sites (ERBSs). The ERBSs anchoring differential chromatin loops with either a gene's promoter or distal regions were correlated with larger transcriptional responses to estrogen compared with ERBSs not involved in differential 3D genome interactions. To functionally test this observation, CRISPR-based Enhancer-i was used to deactivate specific ERBSs, which revealed a wide range of effects on the transcriptional response to estrogen. However, these effects are only subtly and not significantly stronger for ERBSs in differential chromatin loops. In addition, we observed an enrichment of 3D genome interactions between the promoters of estrogen-upregulated genes and found that looped promoters can work together cooperatively. Overall, our work reveals that estrogen treatment causes large changes in 3D genome structure in endometrial cancer cells; however, these changes are not required for a regulatory region to contribute to an estrogen transcriptional response.
10.1101/gr.279699.124